2023
DOI: 10.1038/s41467-023-39152-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct laser writing of 3D electrodes on flexible substrates

Abstract: This report describes a 3D microelectrode array integrated on a thin-film flexible cable for neural recording in small animals. The fabrication process combines traditional silicon thin-film processing techniques and direct laser writing of 3D structures at micron resolution via two-photon lithography. Direct laser-writing of 3D-printed electrodes has been described before, but this report is the first to provide a method for producing high-aspect-ratio structures. One prototype, a 16-channel array with 300 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…1b), with a strong emphasis on biocompatibility and mechanical exibility. We encase gold wiring in a polyimide lm about 4 µm thick, taking advantage of polyimide's proven MEMS process stability and biocompatibility 42,43 . The multistep fabrication sequence includes metal desposition, polyimide solidi cation, gold evaporation, and another polyimide layer, followed by Reactive Ion Etching (RIE) device etching to expose the recording sites, bonding pads, and vias.…”
Section: Resultsmentioning
confidence: 99%
“…1b), with a strong emphasis on biocompatibility and mechanical exibility. We encase gold wiring in a polyimide lm about 4 µm thick, taking advantage of polyimide's proven MEMS process stability and biocompatibility 42,43 . The multistep fabrication sequence includes metal desposition, polyimide solidi cation, gold evaporation, and another polyimide layer, followed by Reactive Ion Etching (RIE) device etching to expose the recording sites, bonding pads, and vias.…”
Section: Resultsmentioning
confidence: 99%
“…Such process was demonstrated for 100 µm pixels, but it is difficult to scale it down to much smaller pixel pitch, such as 20 µm. Another approach could be based on 3D polymer structures, which can be formed by 2photon laser lithography and subsequently metalized for conduction [30][31][32]. However, polymer features (pillars or walls) of high aspect ratio tend to deform over time, leading to cracking of the metal coating.…”
Section: Discussionmentioning
confidence: 99%
“…Laser technology is widely used in the field of flexible material manufacturing and can be used for the fabrication of bio-sensors, soft electronic devices and e-skin. [98][99][100][101][102][103] In a recent study, three-dimensional integrated electronic devices made of elastomers were reported, where laser ablation and controlled soldering were used to create vertical interconnect accesses (VIA). The pattern designs of the electrodes, heaters, and VIA connectors were all fabricated using the laser ablation technique (Fig.…”
Section: Human-machine Interface Based On Soft E-skinmentioning
confidence: 99%